Changing Rules and Configurations During Soccer Small-Sided and Conditioned Games. How Does It Impact Teams’ Tactical Behavior? - Machado, João Cláudio; Ribeiro, João; Palheta, Carlos Ewerton; Alcântara, Chellsea; Barreira, Daniel; Guilherme, José; Garganta, Júlio; Scaglia, Alcides José (Frontiers in Psychology, 2019)
The present study aimed to investigate how team’s tactical behavior varies within and between age categories in different Small-Sided and Conditioned Games’ configurations and conditions. Twenty non-elite youth male soccer players (U15, n=10, mean age=13.5±1.2 years; U17, n=10, mean age=16.3±0.5 years) were selected. Thirty-six Small-Sided and Conditioned Games (SSCG) were played in both categories, namely three Representative SSCG (R-SSCG), three Maintaining Ball Possession Games (MBPG) and three Progression to Target Games (PTG) performed for each configuration (Gk+3vs3+Gk and Gk+4vs4+Gk). Teams’ tactical behavior was analyzed based on simple and composite performance indicators, as well as through Lag Sequential Analysis. Rules manipulation and SSCG configurations influenced teams’ tactical behavior on both categories, but in different ways. Teams composed by younger players presented greater difficulties in MBPG played in smaller games configuration, while Gk+4vs4+Gk configuration can be used to enhance teams’ tactical performance of younger players in R-SSCG and MBPG conditions. Moreover, increasing rules manipulations appeared to negatively impact on teams’ exploratory behavior. Therefore, practitioners should carefully manipulate key constraints to adapt task demands to players’/students age category and training session’s goals in order to enhance tactical performance.